Solving the Problem of Serum Utilization in KazaÐºhstan - Ospanov, Assan; Zhakupova, Gulmira; Toxanbayeva, Botagoz (International Journal of Engineering and Technology, 2018)
The article presents the results of experimental studies of serum beverage enriched with pine bark extract as a source of polyphenols. The effect of pine bark extract is investigated, its use in the production of serum beverage is justified, and the increase of essential amino acids, namely phenylalanine and tyrosine, is established. Enrichment with specially selected herbal components of the serum will allow the creation of new technologies of products with a given therapeutic and preventive direction.Â Â